The Study of Crushed Autoclaved Aerated Concrete as Sand Replacement in Concrete - Mohd Affandy, Noor Edelah; A. Majid, Masni (Recent Trends in Civil Engineering and Built Environment, 2024)
Fine aggregate is one of the most important materials in the production of concrete for construction projects. AAC is an eco-friendly and green building materials that is very sustainable. Nowadays, the uses of AAC in Malaysia is in a great demand due to rapid urbanization of development that needs to implement the quality of AAC properties. Therefore, AAC is used as the fine aggregate partial replacement in the concrete mixture. The main objective of this study is to determine the physical properties of concrete such as workability, density and mechanical properties such as compressive strength. The AAC blocks was crush to produce AAC aggregate as the partial sand replacement in concrete. The properties of concrete will be tested. There were five concrete mixtures with crushed AAC as the replacement of sand were prepared and tested. The mixture of concrete was partially replaced by 0%, 10%, 20, 30% and 40% of CAAC replacement with concrete grade of 30. A total of 30 specimens of concrete cubes with the dimension of 100mm × 100mm × 100mm were tested for the compressive strength after 7 and 28 days of curing. The compressive strength of concrete mix with CAAC is higher at the age specimen of 28 days for it is the ideal design of concrete.  The allowable addition of CAAC replacement in the concrete mix should not be greater than 20%. Besides, the workability of concrete is in medium workability range. The higher the percentage of CAAC replacement, the density and compressive strength of concrete is reduced.